AYAM SEBAGAI INSPIRASI DALAM KARYA SENI GRAFIS - ADRI FERNANDES, Drs. Irwan, M.Sn. Yofita Sandra, S.Pd., M.Pd. (Universitas Negeri Padang, 2018)
The purpose of creating chicken as resemble human behavior. That is an inspiration in the work of graphic art with the technique of serigraphy. Chicken resemblance to human behavior. Is represent a half of human chiken in keeping relationship with spouse giving children and take good care of there.The method of creating works of art, using five stages: Preparation (tools and materials), elaboration stage, sistensis, concept realization, and Settlement. From several stages in the process of creating works of art has created ten graphic works in this final paper.This final work describes of chickens behavior that are similar to human behavior, from how to pair, give birth and take care of their children. The visual form of the work in the box with the title: Pejantan, Balanced, Fighting, crowing, Wingspan, Pair, Waiting, New Generation, Parent, Group.Keywords: Chicken Behavior and Human Behavior, Metaphors, Ideas, Graphics.